PEMBELAJARAN MODEL STAD UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA PADA SISWA KELAS V SDN 39 CAKRANEGARA - Ni Nyoman Mariani Artini (Jurnal Paedagogy, 2016)
This study aims to improve mathematics learning achievement in fifth grade students of SDN 39 Cakranegara by using the STAD (Student Team Achievement Division) learning model. This research method uses classroom action research (PTK). This research was conducted in 2 cycles based on the material divided into two, namely understanding the properties and simple building nets and calculating the volume of cubes and blocks. The subjects of this classroom action research were students of class V SDN 39 Cakranegara with a total of 28 students, consisting of 15 male students and 13 female students. This research instrument uses; observation sheets for teachers, observation sheets for students, student response questionnaires, field note formats, student worksheets, and final cycle test question sheets. Data analysis in this study used qualitative and quantitative descriptive analysis. The results of this study are efforts to improve student learning outcomes with the STAD (Student Team Achievement Division) Model Learning method, which has been able to improve student learning outcomes. This increase occurred in cycle I and cycle II with evidence of an increase in: (1) Implementation of learning mathematical concepts in building materials using the STAD (Student Team Achievement Division) learning model, in class V SDN 39 cakranegara proved to be able to improve student understanding, this is based on the results of observations on student activity and if the percentage of pre-cycle is 12.90%, cycle 1 is 29.03%, in cycle 2 it increases again to 90.32%. (2) The use of the STAD (Student Team Achievement Division) learning model, in learning to build a room in class V SDN39 Cakranegara, is proven to improve student learning outcomes, this can be seen from the acquisition of class average scores from student test results at each stage of the cycle. The increase is, the class average value in pre-cycle is 50, in cycle I is 60.70 and in cycle II is 75.35.